Methotrexate monotherapy and methotrexate combination therapy with traditional and biologic disease modifying antirheumatic drugs for rheumatoid arthritis: abridged Cochrane systematic review and network meta-analysis. (21st April 2016) - Hazlewood, Glen S; Barnabe, Cheryl; Tomlinson, George; Marshall, Deborah; Devoe, Dan; Bombardier, Claire
Abstract : Objective  To compare methotrexate based disease modifying antirheumatic drug (DMARD) treatments for rheumatoid arthritis in patients naive to or with an inadequate response to methotrexate. Design  Systematic review and Bayesian random effects network meta-analysis of trials assessing methotrexate used alone or in combination with other conventional synthetic DMARDs, biologic drugs, or tofacitinib in adult patients with rheumatoid arthritis. Data sources  Trials were identified from Medline, Embase, and Central databases from inception to 19 January 2016; abstracts from two major rheumatology meetings from 2009 to 2015; two trial registers; and hand searches of Cochrane reviews. Study selection criteria  Randomized or quasi-randomized trials that compared methotrexate with any other DMARD or combination of DMARDs and contributed to the network of evidence between the treatments of interest. Main outcomes  American College of Rheumatology (ACR) 50 response (major clinical improvement), radiographic progression, and withdrawals due to adverse events. A comparison between two treatments was considered statistically significant if its credible interval excluded the null effect, indicating >97.5% probability that one treatment was superior. Results  158 trials were included, with between 10 and 53 trials available for each outcome. In methotrexate naive patients, several treatments were statistically superior to oral methotrexate for ACR50 response: sulfasalazine and hydroxychloroquine ("triple therapy"), several biologics (abatacept, adalimumab, etanercept, infliximab, rituximab, tocilizumab), and tofacitinib. The estimated probability of ACR50 response was similar between these treatments (range 56-67%), compared with 41% with methotrexate. Methotrexate combined with adalimumab, etanercept, certolizumab, or infliximab was statistically superior to oral methotrexate for inhibiting radiographic progression, but the estimated mean change over one year with all treatments was less than the minimal clinically important difference of 5 units on the Sharp-van der Heijde scale. Triple therapy had statistically fewer withdrawals due to adverse events than methotrexate plus infliximab. After an inadequate response to methotrexate, several treatments were statistically superior to oral methotrexate for ACR50 response: triple therapy, methotrexate plus hydroxychloroquine, methotrexate plus leflunomide, methotrexate plus intramuscular gold, methotrexate plus most biologics, and methotrexate plus tofacitinib. The probability of response was 61% with triple therapy and ranged widely (27-70%) with other treatments. No treatment was statistically superior to oral methotrexate for inhibiting radiographic progression. Methotrexate plus abatacept had a statistically lower rate of withdrawals due to adverse events than several treatments. Conclusions  Triple therapy (methotrexate plus sulfasalazine plus hydroxychloroquine) and most regimens combining biologic DMARDs with methotrexate were effective in controlling disease activity, and all were generally well tolerated in both methotrexate naive and methotrexate exposed patients.